Diversity Management in the Ghanaian Health Sector: A Case Study of the NHIA - Inweregbu, Cynthia Ngozi (University of the Witwatersrand, Johannesburg, 2024)
Diversity management has become a critical tool in ensuring efficiency and productivity in organisations and societies. Research has recognized several conceptualisations of diversity and provided direction for effective and better ways of implementing diversity management at an organisational and national level. However, it has been contended that emphasis on conceptualising diversity management has mainly been within the context of the western perspective. Diversity management is an emerging aspect of management, which embodies on disciplines such as sociology, psychology, and human resource. The concept of diversity management has assumed global dimension and a context specific approach is required to make it effective. In this regard, it has been established by scholars to be a potent management tool in the globalised world. This call for an approach which suits the African and for that matter the Ghanaian context. To this effect, this research explores the concept, policies, and challenges of diversity management from Ghanaian perspective to assist in fashioning out a context specific strategy to diversity management. A qualitative methodology (case study approach) was employed to answer the research questions and realise the objectives. In line with the tenets of the chosen methodology, which requires data absoluteness, the interviewees and focus group members were selected through purposively sampling. There were thirty-four in-depth interviews and two focus group discussions conducted at the NHIA head office and regional office. Coding and thematic analysis were employed to identify the conceptualisation of diversity, policies in place for diversity management and challenges encountered in relation to diversity management at the NHIA. The results suggests that diversity can be described as differences in ethnic background, political affiliation, gender, religious belief, languages, and age. Further, the result points to the fact that an individual cannot be only identified by one characteristic but several of them. ii Additionally, this study identified couple of areas that needs attention to ensure an effective diversity management at the NHIA. The work environment in NHIA is very diverse and drives the complexity therein. The socio-cultural, religious, and political differences are very entrenched and require an effective diversity framework that ensures the presence of critical elements such as appreciation of uniqueness and the sense of belonging. Subsequently, a model was developed from the findings of the study to highlight the critical elements driving the dynamics of diversity management in NHIA. Additionally, the identified elements serve as tools which can be employed to allay the challenges encountered in ensuring effective management of diversity in NHIA and similar environments. Future studies may be conducted to validate the framework developed in this study and establish generalisabilty in the health industry and in other public organisations. A comparative case study research focusing on a private and public sector could also enrich the framework
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: diversity; diversity management; SDG-3: Good health and well-being